Computer-aided design & 3D printing of adolescent idiopathic scoliosis brace - Yeo, Guoli (Nanyang Technological University, 2022)
Adolescent idiopathic scoliosis (AIS) is a three-dimensional curvature of the spine. It is the most common form of scoliosis, affecting children aged 10 to 18. Scoliosis can be categorized into three groups – idiopathic, congenital, and neuromuscular.